Organizational Climate and Teachers’ Morale: Developing a Specific Tool for the School Context – A Research Project in Italy - Converso, Daniela; Cortini, Michela; Guidetti, Gloria; Molinengo, Giorgia; Sottimano, Ilaria; Viotti, Sara; Loera, Barbara (Frontiers in Psychology, 2019)
The school context is exposed to several demanding factors relating to student and family needs and external evaluative processes of students’ learning and process outcomes, such as abilities in planning training courses and a learning environment. However, there is a need to develop tools that adequately support schools in making self-assessment evaluations of the internal organizational climate and teacher morale (TM). The present study proposes an Italian version of the School Organizational Health Questionnaire (SOHQ), developed by Hart et al. (2000). An Italian version of the SOHQ was deployed to 9 public primary schools in the north of Italy, and 325 cases were eventually retained as being valid for the analysis. Using confirmatory factor analysis, results highlight that a 56-item version is model fit and presents satisfactory psychometric properties, demonstrating the suitability of a latent structure composed of 12 intercorrelated factors. The present study gives further insight into increasing the use of self-assessment tools in the development of good practices and the monitoring of teacher morale within the school context.